ANALISIS POTENSI PAKAN SERTA INDEKS DAYA DUKUNG WILAYAH TIGA KECAMATAN DI KABUPATEN MAGELANG TERHADAP PENGEMBANGAN TERNAK SAPI PERAH - Sri Desky Eka Viomalini; Lilis Hartati; Danes Suhendra; Yosephine Laura Reynardia Esti Nugrahini (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Magelang Regency is a district with an area of 1.085,73 km2 with an agricultural land area of 78,897 Ha consisting of wetland with  36,974 Ha and dryland with  41,923 Ha. The total population of dairy cattle in Magelang Regency is 503, while the need for milk reaches 8.184,61 liters/year. This research aims to find out and provide information regarding the potential amount of forage availability and the regional carrying capacity index in supporting the development of dairy cattle. The data collection method used is a survey method with samples taken from Grabag District, Sawangan District, and Ngablak District with data consisting of the identity of livestock ownership, number and type of livestock owned, origin of feed, and kind of feed used, as well as harvest area. The data analysis method that is used is descriptive analysis.  The results of the research show the potential of agricultural products in 2021 consisting of waste products from corn straw, peanuts, sweet potatoes, and cassava in Ngablak District, Sawangan District, and Grabag District is 796.962 tons, the potential for natural forage is 16.638,6 tons, the carrying capacity of dairy cattle is 2.892,3 ST, the Carrying Capacity Index (IDD) is 2.273,6 and this is included in the safe criteria which still has great potential to be used as a dairy cattle development area.